2017
DOI: 10.5812/jjm.14341
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbapenem-Resistant Klebsiella pneumoniae Species Isolated From a Tertiary Hospital, Ankara, Turkey

Abstract: Background: Carbapenem-resistant Klebsiella pneumoniae isolates can spread among the hospitalized patients and result in serious infections and increase mortality. Molecular studies provide useful information about resistance mechanisms and crosstransmission among the resistant isolates. Objectives: The current study aimed at investigating phenotypic and molecular characteristics of the carbapenem resistance and clonal relationship among the K. pneumoniae isolates recovered from infection sites and rectal swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…When we evaluated the distribution of the clinical samples, we observed that carbapenemaseproducing Enterobacteriaceae strains were found in urine, blood, wound swab, and tracheal aspirate cultures in the decreasing order of frequency at rates of 51%, 24%, 15%, and 10%, respectively. Similar to our study results, other studies reported that urine and blood samples were the leading sample types with the highest frequencies (4,(12)(13)(14).…”
Section: Carbapenemase-producingsupporting
confidence: 92%
See 1 more Smart Citation
“…When we evaluated the distribution of the clinical samples, we observed that carbapenemaseproducing Enterobacteriaceae strains were found in urine, blood, wound swab, and tracheal aspirate cultures in the decreasing order of frequency at rates of 51%, 24%, 15%, and 10%, respectively. Similar to our study results, other studies reported that urine and blood samples were the leading sample types with the highest frequencies (4,(12)(13)(14).…”
Section: Carbapenemase-producingsupporting
confidence: 92%
“…The blaOXA-48 gene was found in 88.8% of K. pneumoniae isolates and 11.1% of E. coli isolates. In a study, Çelikbilek et al found out that more than 90% of carbapenem-resistant K. pneumoniae isolates were blaOXA-48 positive (13). A multicenter study that included patients from various regions of Turkey reported a high prevalence rate (83%) for the presence of the blaOXA-48 gene in CRE.…”
Section: Carbapenemase-producingmentioning
confidence: 99%
“…Molecular categorization using PFGE showed considerable similarity among K. pneumoniae isolates and moderate clonal relatedness suggesting the spread of these XDR isolates across the hospital. This cross-contamination might be resulting from hospital staff, infected or colonized patients, and/or contaminated instruments (Celikbilek et al, 2017). There were 14 different pulsotypes among the isolates, which were grouped into four clusters.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, blaOXA-48 and blaNDM-1 were detected in 90.3% and 6.5% of the carbapenem-resistant isolates, respectively. Due to the high rate of carbapenem resistance and 80.6% clonal relationship by pulsed-field gel electrophoresis (PFGE) in a 3-years period, the authors suggested that CRKP isolates pose a potential threat for patients to get hospital-acquired infections [10]. In Turkey, the blaOXA-48 genes were identified previously in K. pneumoniae, E. aerogenes, E. coli, C. freundii, E. cloacae, S. marcescens, P. rettgeri, K. oxytoca, P. mirabilis, M. morganii, P. stuartii, R. planticola, and A.baumanii.…”
Section: Discussionmentioning
confidence: 99%
“…A bacterial suspension equal to four McFarland turbidity was prepared in Phosphate Buffered Saline (PBS, Sigma, Germany) and boiled for 10 minutes. Then, it was centrifuged for 2 minutes at 13000 g and the supernatant was used as the DNA source [10]. PCR reaction was established by using 10 pmol of each primer, and 2.5 U of Taq DNA polymerase (Thermo Scientific-Fermantas Corporation, Vilnius, Lithuania) in a final reaction volume of 50 μL.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%